Development of a Flipbook-Based E-Module on Linear Programming for Mathematics Education Students - Zuida Ratih Hendrastuti; Yesi Franita; Sherla Salsabila Adawiyah; Bagas Ardiyanto (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2025)
This study aims to develop a flipbook-based e-module on linear programming material for students that meets the criteria of validity, practicality, and effectiveness, making it suitable for learning. This study uses the Research and Development (R&D) method with the ADDIE development model which includes five stages, namely: Analysis, Design, Development, Implementation; and Evaluation. The research instruments included an expert validation sheet, a student response questionnaire, and a learning outcome test. The e-module's validity was assessed by subject-matter, media, and language experts using a 1–5 Likert scale, yielding an average score of 126 (max 135), indicating very high validity. Practicality was measured through student responses on ease of use, display, and learning benefits, with 52.5% rating it as very practical and 47.5% as practical. The e-module's effectiveness was assessed based on student learning outcomes, with a mean of 90.25 and 97.5% achieving scores above the Minimum Completion Level (≥75). The results indicate that this flipbook-based e-module is valid, practical, and effective for use in linear programming lectures. Consequently, this e-module has the potential to improve the quality of mathematics learning, particularly in understanding linear programming concepts, and to encourage student independence in learning through an interactive, accessible presentation of materials.